2007
DOI: 10.1186/1471-230x-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Septic thrombophlebitis of the superior mesenteric vein and multiple liver abscesses in a patient with Crohn's disease at onset

Abstract: Background: Portal-mesenteric vein thrombosis, pylephlebitis and liver abscesses are rare complications of inflammatory bowel disease (IBD). The purpose of this case report is to relate an unusual presentation of CD in order to show how conservative treatment could be an appropriate option as a bridge to the surgery, in patients with septic thrombophlebitis and multiple liver abscesses with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 10 publications
0
25
0
3
Order By: Relevance
“…Rarely, mesenteric septic thrombophlebitis may be observed in the setting of small bowel Crohn disease. When mesenteric venous thrombosis is noted, the liver should be carefully evaluated for abscesses (24). Spectral Doppler US has also been used to assess the mesenteric vasculature in patients with Crohn disease, although some researchers have concluded that spectral Doppler US findings do not reliably correlate with disease activity (11,25).…”
Section: Mesenteric Findings Inflammationmentioning
confidence: 99%
“…Rarely, mesenteric septic thrombophlebitis may be observed in the setting of small bowel Crohn disease. When mesenteric venous thrombosis is noted, the liver should be carefully evaluated for abscesses (24). Spectral Doppler US has also been used to assess the mesenteric vasculature in patients with Crohn disease, although some researchers have concluded that spectral Doppler US findings do not reliably correlate with disease activity (11,25).…”
Section: Mesenteric Findings Inflammationmentioning
confidence: 99%
“…In the shift analysis (analysis of change in the distribution of outcomes across an ordinal scale), a statistical test searches for evidence of a favorable shift toward wellness, e.g. in the distribution of the mRS scores across the range of disabilities in the treated group versus the placebo control group [4]. It has been argued that a shift analysis takes into account the full range of treatment effects across the range of disabilities on an outcome scale while a dichotomized approach privileges a single health transition state as a clinically meaningful treatment effect and discards other potentially salient outcomes [5].…”
Section: Introductionmentioning
confidence: 99%
“…[62] While these microbiota frequently do not cause sepsis, sepsis is significantly commoner in IBD, both in immunosuppressed patients and in patients who are newly diagnosed and not on immunosuppressive therapy. [63][64] An increased incidence of bacterial endocarditis in both UC and CD has also been reported. [65] Rifaximin appears to be a promising antibiotic in inducing remission of CD (69% in open studies and significantly better than placebo in double blind trials) and UC (76% in open studies and significantly better than placebo in controlled studies).…”
Section: Inflammatory Bowel Disease and Sepsismentioning
confidence: 99%